GUIDELINES FOR DEVELOPMENT INSTRUCTIONAL LEADERSHIP OF TEACHERS IN SCHOOL UNDER THE SECONDARY EDUCATIONAL SERVICE AREA OFFICE LOEI NONG BUA LAM PHU - Hrutkhong, Amporn; Banwiset, Suchart; Nuntee, Sakdinaporn (Journal of Srilanchang Review, 2024)
The objectives of this research were as follows: 1) To study the current conditions, desirable conditions, and priority needs of development instructional leadership of teacher in school. 2) To create the guidelines and 3) To evaluate the guidelines. The research process is divided into three phases: phase 1: study the current situation, desired condition, and needs assessment. The sample consisted of 93 school administrators and 322 teachers, totaling 415 individuals, determined using the sample size criteria of Krejcie & Morgan, and employing stratified random sampling. The research instrument used was a questionnaire. Phase 2: develop guidelines for enhancing teachers’ academic leadership in schools, which includes three steps: Conduct in-depth interviews with three school administrators using a semi-structured interview format. Create guidelines for improving teachers’ academic leadership in schools. Conduct focus group discussions with nine experts, using focus group discussion records as research instruments. Phase 3: evaluate the guidelines for enhancing teachers’ academic leadership in schools through expert assessment involving five experts. The evaluation tool was an expert assessment form. Statistical analysis for quantitative data included frequency, percentage, mean, standard deviation, and the modified priority needs index, along with qualitative data analysis through descriptive analysis. The results were as follows: Overall, the current conditions of development instructional leadership of teacher in school were at a high level while the desirable conditions were at the highest level. The modified priority needs index for development instructional leadership of teacher in school were as follows: 1) development of media, innovation, and educational technology, 2) self-development and peer development, 3) curriculum development, 4) learning process management, and 5) student development. Guidelines for enhancing teachers’ academic leadership in schools comprised five areas: 1) Development of media, innovation, and educational technology. 2)Self-development and peer teacher development. 3) Curriculum development. 4) Learning process management and 5) Student development. Upon examining the modified priority needs index, the top three areas included specific implementation strategies: 1)For the development of media, innovation, and educational technology, schools should encourage teachers to use technology to produce media and innovations, and organize knowledge-sharing activities regarding the use of educational technologies to enhance student learning. 2) For self-development and peer teacher development, schools should plan and promote teachers to take the lead in teaching and foster a vision for self-improvement, including collaborative observations of teaching or classroom supervision among peers. And 3) for curriculum development, schools should organize activities to develop teachers’ capabilities in creating and improving curricula, encouraging teachers to analyze the outcomes of curriculum implementation for refinement, and supporting teachers to conduct research aimed at curriculum development that meets local needs, with a focus on students. The overall assessment level of the development instructional leadership of teacher in school was the highest. The order, from highest to lowest, is utility (x ̅ = 4.89, S.D. = 0.25), propriety (x ̅ = 4.79, S.D. = 0.40), and feasibility (x ̅ = 4.71, S.D. = 0.47) respectively. Keyword: Guidelines for development; Instructional leadership